Cerebriform patterns in dermatology - Anup Kumar Tiwary (Our Dermatology Online, 2021)
Dermatology has vast spectrum of mucocutaneous manifestations in respect of morphology of the lesions, their arrangement, distribution and other feature. Cerebriform pattern is one of many interesting presentation which has been described in some skin conditions in English literature. Here in this article, those conditions have been compiled and described in brief.